Flavonoids and anthocyanins from the leaves of the Pride of Burma (Amherstia nobilis). (April 2022) - Iwashina, Tsukasa; Tanaka, Nobuyuki; Aung, Mu Mu; Devkota, Hari Prasad; Mizuno, Takayuki
Abstract: Three flavonols, two flavones and six C -glycosylflavones were isolated from the mature leaves of the Pride of Burma ( Amherstia nobilis ) endemic to Myanmar. In addition, three anthocyanins were isolated from the dark red sprouting leaves of the species, together with the flavonoids in the mature leaves. They were identified as quercetin 3- O -glucoside (1 ), 3′- O -glucoside (2 ) and 3- O -xyloside (3 ) (flavonols), luteolin 7- O -glucoside (4 ) and tricin 7- O -glucoside (5 ) (flavones), vitexin (6 ), isovitexin (7 ), vitexin 2''- O -xyloside (8 ), isovitexin 2''- O -xyloside (9 ), vitexin 2''- O -glucoside (10 ) and vitexin 2''- O -rhamnoside (11 ) ( C -glycosylflavones), and cyanidin 3- O -glucoside (12 ), 3- O -xyloside (13 ) and peonidin 3- O -glucoside (14 ) (anthocyanins). Although the flavonoids of the flowers have been reported, this is the first report of the flavonoids from the leaves of this species. Flavonoid composition of A. nobilis was chemotaxonomically compared with those of phylogenetically related genera. Graphical abstract: Image 1 Highlight: Flavonoids and anthocyanins from the leaves of Amherstia nobilis were surveyed. Three flavonols, two flavones, six C -glycosylflavones and three anthocyanins were isolated and identified. Foliar flavonoids of Amherstia were reported for the first time and discussed those of related genera.